Analytical calculation of stress concentrations at welded flange necks. Issue 6 (7th May 2020) - Seidel, Marc
Abstract: Ring flange connections for tubular towers, such as those for wind turbines or chimneys, are subjected to significant fatigue loading. Apart from the bolts, it is also necessary to carry out a fatigue analysis of the weld connecting the flange to the tower shell. Owing to the presence of the flange, local bending moments occur in the shell which increase the nominal (membrane) stresses, i. e. stress concentrations occur. This paper presents an analytical model for calculating these local bending moments such that stress concentrations can be determined. The analytical model was compared with results from 3D finite element models, and good agreement was found. The results from the model presented are thus deemed appropriate for design purposes. Abstract: Analytische Berechnung von Spannungskonzentrationen an Schweißnähten von Ringflanschverbindungen Ringflanschverbindungen für Rohrtürme, wie solche für Windenergieanlagen oder Schornsteine, sind einer erheblichen Ermüdungsbeanspruchung ausgesetzt. Neben den Schrauben muss auch die Schweißnaht, die den Flansch mit der Turmschale verbindet, gegen Ermüdungsversagen abgesichert werden. Aufgrund des Vorhandenseins des Flansches treten lokale Biegemomente in der Schale auf, die die nominelle Membranspannung erhöhen, d. h., es treten Spannungskonzentrationen auf. In dieser Arbeit wird ein analytisches Modell vorgestellt, um solche lokalen Biegemomente zu berechnen, sodass Spannungskonzentrationen bestimmt werden können. Das analytische Modell wird mit den Ergebnissen von 3D‐Finite‐Elemente‐Modellen verglichen, wobei eine gute Übereinstimmung festgestellt wird. Die Ergebnisse des vorgestellten Modells werden daher für Entwurfszwecke als angemessen erachtet.